Approximation of the Characteristic Functions - Using the Fuzzy Approach - Pokorny, M. (Radioengineering Society, 1995)
To approximate the real characteristic functions of the non-linear electronic elements various mathematical methods are used. Such methods offer the analytic approximating mathematical expressions as their results. One of the interesting non-conventional method for the approximation task is the approach of the fuzzy sets theory and fuzzy multivalue linquistic logic. To apply of this method we obtain the approximation functions of the non-linear fuzzy rule based form. To design of such fuzzy model we use the approaches of the fuzzy non-linear regression analysis. The article describes the structural and parameters identification of such model and introduces the results of the numerical experiments.
Keywords: fuzzy regression analysis; fuzzy conditional rule; fuzzy non-linear model